A Comparative Analysis of Tourism, Hospitality and Catering: Strategic Development and Sustainable Practices in China and Gabon (International Journal of Scientific Research and Management (IJSRM), 2024)
This research conducts a comparative analysis of the tourism, hospitality, and catering industries in China and Gabon, highlighting their strategic development and sustainable practices. China’s tourism industry, marked by extensive government investment and rapid modernization, has grown significantly since the late 20th century, making the country a leading global destination. Major attractions such as the Great Wall and Zhangjiajie National Forest Park, alongside government policies promoting domestic tourism and sustainability, have been pivotal to its success. In contrast, Gabon’s tourism sector, rich in biodiversity and cultural heritage, remains underdeveloped due to infrastructure challenges and limited global visibility. Despite these hurdles, Gabon has made strides in promoting ecotourism through initiatives like the establishment of national parks. The study reveals stark contrasts in the infrastructure, government policies, and market segments between the two countries, with China focusing on technological integration and market diversification, while Gabon emphasizes conservation and sustainable tourism. Recommendations for both nations include enhancing sustainable practices, improving infrastructure, and leveraging technology to boost tourism growth. The findings underscore the potential for both countries to expand their tourism sectors in a sustainable and inclusive manner, contributing to economic diversification and environmental preservation